1991
DOI: 10.1095/biolreprod44.3.561
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Androgen Receptor in the Follicle and Corpus Luteum of the Primate Ovary during the Menstrual Cycle1

Abstract: Ovarian androgens may act locally to modulate follicular and luteal function in various species. This study examined the distribution of androgen receptors within the primate ovary throughout the menstrual cycle. Ovaries were collected from rhesus and cynomolgus monkeys during the early, mid-, and late (n = 3-5 per stage) follicular and luteal phases of the cycle. The tissues were processed for indirect immunocytochemical localization of androgen receptors with a specific monoclonal antibody against human andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 27 publications
3
41
0
2
Order By: Relevance
“…This effect may not be specific to progestin since androgen replacement was also associated with increased progesterone production in some animals. Immunocytochemical evidence for androgen receptors in the macaque (39) and human (40) corpus luteum support a function for androgens in luteal development and/or function. Furthermore, the duration of progesterone inhibition during the gonadotropin surge may have differential effects on subsequent luteal development.…”
Section: Discussionmentioning
confidence: 89%
“…This effect may not be specific to progestin since androgen replacement was also associated with increased progesterone production in some animals. Immunocytochemical evidence for androgen receptors in the macaque (39) and human (40) corpus luteum support a function for androgens in luteal development and/or function. Furthermore, the duration of progesterone inhibition during the gonadotropin surge may have differential effects on subsequent luteal development.…”
Section: Discussionmentioning
confidence: 89%
“…These results suggest a progestational rather than an estrogenic regulation of ovarian function in the monkey. Hild-Petito et al (1991) have also demon-strated the presence of androgen receptors in the granulosa and theca cells of growing monkey follicles, and a paracrinelautocrine function has been ascribed to follicular androgen and its receptors. Iwai et al (1990) have shown immunocytochemically that human granulosa cells possess only estrogen receptors before the preovulatory LH surge; however, estrogen receptors disappear and progesterone receptors appear following the LH surge.…”
Section: Morphological Studies On Follicular Dna Synthesismentioning
confidence: 97%
“…However, the modulation of AR expression by follicular development has not been observed in monkeys (7) and women (8), presumably because of methodological differences (5). Incidentally, in these two latter species, ARs have been detected both in granulosa and thecal cells (7,8).…”
Section: Androgens and Folliculogenesis: Physiologic Bases And Animalmentioning
confidence: 99%